Religious Leaders' Strategy in the Development of Islamic Community in the Aspect of Strengthening Social Welfare - Siska Dindari; Muhammad Iqbal Abdul Muin (Assyfa Journal of Islamic Studies, 2026)
This study aims to analyze the strategies of religious leaders in supporting the social welfare of the community in Pulau Tanjung Village, Teluk Dalam District, Asahan Regency. This research is a field study with a descriptive qualitative approach. Data were collected through observation, in-depth interviews, and documentation involving religious leaders, village officials, and the community as informants. The results of the study indicate that religious leaders have an important role as motivators, social mediators, and agents of change through social da'wah activities, religious studies, fundraising, and fostering community solidarity. However, the strategies implemented are still incidental and have not been systematically integrated due to limited resources and coordination. This study contributes to the development of sociological studies of religion by emphasizing the important role of religious leaders in strengthening social solidarity and the welfare of village communities. The findings of this study emphasize the need for a more planned and collaborative strategy to improve the social welfare of the community in a sustainable manner. This research focuses on shifting focus from conventional da'wah strategies to a multidimensional approach that integrates digital literacy and strengthening the productive economy to mitigate social inequality. While previous literature has focused more on the role of religious leaders in consumer philanthropy (providing direct aid), this research offers a novelty through an analysis of religious leaders' strategies as catalysts for community empowerment that utilize digital ecosystems for transparent access to welfare and strengthening community-based economic resilience amidst the challenges of the disruptive era.